Sensitivity of Gifted Students at University - Mahmoud. M (Al-Qanṭara, 2022)
Abstract The study aimed to determine the degree of hypersensitivity of gifted students at Al Ain University and how it differs regarding variables of gender (male, female) and class (fifth, seventh). The study sample comprised (62) male and female students. (30) male students (13 fifth grade and 17 seventh grade), and (32) female students (19 fifth grade and 13 Seventh grade). The study used the descriptive method through a questionnaire prepared by the two researchers to collect data. The findings showed that the degree of sensitivity of gifted students was average or high. The findings also showed that there was a difference with statistical function attributed to gifted students in favor of males and that there were no differences with statistical function attributed to class variable (fifth, seventh). The study came up with several recommendations.